Potential role of microbial surfactants in environment control recovered from oil contaminated and non-contaminated sites - Prasad, Bhairav; Sharma, Kanika; Mishra, Mohit (Recent Research in Science and Technology, 2013)
A total of 20 samples were collected from contaminated (oil contaminated) as well as non-contaminated (agricultural) sites. A total of 10 bacterial isolates were recovered from these samples out of which 6 were recovered from non contaminated sites and 4 were recovered from contaminated sites gave emulsification index ranged from 44% to 73%. Different carbon sources viz. maltose, starch, sucrose, mannitol and nitrogen sources viz. urea, peptone, potassium nitrate and ammonium nitrate were screened to obtain optimum emulsification activity by KMSS09 and KIWS11. In this study mannitol and peptone was evaluated as best carbon and nitrogen source for the production of bioemulsifier. Further these potential isolates were evaluated for some environmental applications viz. Microbial Enhanced Oil Recovery and Bacterial Adhesion to Hydrocarbon assay having important role in bioremediation. The percentage oil recovered by KMSS09, KIWS11 and P. aeruginosa MTCC 2297 was 51.67%, 71.67% and 85.0% respectively. In BATH assay, percentage of bacterial adherence by KMSS09, KIWS11 and P. aeruginosa MTCC 2297 was 80.4%, 86.3% and 93.2% respectively showing wide applicability in bioremediation for pollution remediation of metal and hydrocarbon contaminated field.